DEVELOPING THE ABILITY OF ELEMENTARY STUDENTS METAPHORICAL THINKING THE CITARUM THROUGH THE REALISTIC MATHEMATICS EDUCATION APPROACH - Sukma Murni; Sylvia Rabbani (IKIP Siliwangi, 2019)
This study aims to determine the development of mathematical Metaphorical Thinking capabilities of Bantaran Citarum Elementary School students through a Realistic Mathematics Education (RME) approach better than those using ordinary learning. The method used in this study was a quasi-experimental method carried out in one of the elementary schools in Dayeuh Kolot Subdistrict, Bandung Regency. Data collection uses the results of pretest and posttest mathematical Metaphorical Thinking abilities. To get the research data, the instrument was used in the form of a mathematical Metaphorical Thinking ability test. Data analysis is done quantitatively, quantitative analysis is carried out on the ability of Metaphorical Thinking. In calculating data processing using Microsoft Excel and SPSS 23. The results showed that the development of mathematical Metaphorical Thinking capabilities which learning using the RME approach was better than those using ordinary learning. Keywords: Metaphorical Thinking, Realistic Mathematics Education.